A revision of the genus Arenopontia Kunz, 1937 (Copepoda, Harpacticoida, Arenopontiidae), including the description of five new species - Sak, Serdar; Karaytuğ, Süphan; Huys, Rony (Zootaxa, 2024)
A revision of the genus Arenopontia Kunz, 1937 (Harpacticoida, Arenopontiidae) is presented based on morphological examination of a wide range of material. The genus, as redefined herein, encompasses A. subterranea Kunz, 1937 (type species by monotypy), A. problematica Masry, 1970, A. nesaie Cottarelli, 1975 and A. riedli Lindgren, 1976, in addition to five new species from European waters: A. adriatica sp. nov., A. anatolica sp. nov., A. basibuyuki sp. nov., A. gunduzi sp. nov. and A. syltensis sp. nov. Arenopontia pontica Apostolov, 1969 is considered unidentifiable and confirmed as a species inquirenda. The widely accepted notion that A. subterranea represents a cosmopolitan species displaying high intraspecific variability is rejected. Previous illustrated records attributed to the type species are critically reassessed and indicate that future examination of additional material from sandy beaches in the Northern Hemisphere will lead to further splintering of “A. subterranea” into a complex of cryptic lineages. Arenopontia subterranea and A. syltensis sp. nov. occur sympatrically on the Isle of Sylt while extensive sampling in the Black Sea revealed a similar overlap in distribution between A. anatolica sp. nov. and A. basibuyuki sp. nov. This study provides yet another example of how rigorous morphology-based analysis of pseudocosmopolitan taxa allows resolution of previously unrecognized cryptic status into multiple named species without recourse to molecular sequence data. A key to the nine valid species of Arenopontia is presented and distribution data for each species are collated.